Social Domination and Marginalization in Shirley Jackson’s The Lottery: Critical Discourse Analysis and Appraisal Study - Novalita Pradnya Paramitha (Journal of English Language Teaching and Linguistics, 2021)
Ideology is sometimes hidden away, especially in language, since language is the closest aspect of human, for it is used every day. One of the examples is covert ideology within the short story. This is why critical discourse analysis is needed to uncover this kind of thing. The short story scrutinized in this research is Shirley Jackson’s The Lottery. In order not to merely reveal an assumption, this research combines the critical discourse analysis theory by Fairclough, specifically termed Dialectical-Relational approach, as the philosophical theory with Appraisal study as the linguistic theory. All of the sentences and clauses in the story are the data of the research. The data, then, are close read for more accurate analysis. It is observed that the ideologies concealed by the text are social domination and marginalization through tradition. However, those social wrongs are hard to abolish, since they are even desired by the society; the tradition is believed to bring prosperity to the village regardless of wicked impact to the individual it brings, related to metanarratives, doxa, and symbolic violence, and fidelity towards the actor of domination. Therefore, there should be law to govern the habit harmful for others, so that all of the society rights can be protected.